2011
DOI: 10.1016/j.meegid.2011.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Skin microbiota: Microbial community structure and its potential association with health and disease

Abstract: Skin, the largest human organ, is a complex and dynamic ecosystem inhabited by a multitude of microorganisms. Host demographics and genetics, human behavior, local and regional environmental characteristics, and transmission events may all potentially drive human skin microbiota variability, resulting in an alteration of microbial community structure. This alteration may have important consequences regarding health and disease outcomes among individuals. More specifically, certain diversity patterns of human m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
180
1
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(190 citation statements)
references
References 85 publications
2
180
1
7
Order By: Relevance
“…aureus is found in abundance in skin of individuals with atopic eczema. 13 This supports the finding in our study where Staphylococcus aureus is found more in middle meatus in patients with allergic rhinitis than in controls.…”
Section: Discussionsupporting
confidence: 92%
“…aureus is found in abundance in skin of individuals with atopic eczema. 13 This supports the finding in our study where Staphylococcus aureus is found more in middle meatus in patients with allergic rhinitis than in controls.…”
Section: Discussionsupporting
confidence: 92%
“…These factors alter the composition of the skin micro-organism community and may influence skin barrier function by inducing an unbalanced state of dysbiosis that may be evidenced in chronic inflammatory skin diseases, such as atopic dermatitis, psoriasis, rosacea, or acne (7,(11)(12)(13) . Factors involved in the relationship between skin microbiota and the skin barrier function are summarized in Table 1. • • Interplay between Skin Cells and Bacteria in Host Defense and Inflammation…”
Section: • Infectionmentioning
confidence: 99%
“…25 The effectiveness of fecal and earwax transplant suggests that the microbiome plays a clinically meaningful role in the maintenance of health. [24][25][26] In AD-affected skin, there is overrepresentation in nonlesional and even more in lesional areas of Firmicutes, including Staphylococci, and underrepresentation of Actinobacteria, Proteobacteria, and Cyanobacteria. 2 Restoring microbial balance on the skin may be clinically meaningful in inflammatory skin diseases, such as atopic dermatitis.…”
Section: Moisturizers Help To Restore the Skin Microbiomementioning
confidence: 99%